A Survey on Parents' Health Literacy on Childhood Human Papilloma Virus Vaccination - Güneş, Ömer; Özkaya-Parlakay, Aslınur; Güney, Ahmet Yasin; Güder, Latife; Mustafaoğlu, Özlem; Bayraktar, Pınar; Kanık-Yüksek, Saliha; Gülhan, Belgin (Journal of Pediatric Infectious Diseases, 2022)
Objective The aim of this study is to determine parents' knowledge levels and attitudes about childhood human papillomavirus (HPV) vaccination and reveal the differences between parents who are health care workers and nonhealth care workers. The HPV vaccine can potentially prevent initial HPV infection and HPV-related genital and anal precancerous disorders and cancers.Methods Questions and attitudes toward childhood HPV vaccination were asked to 564 parents who agreed to participate in the study.Results In our study, the rate of health care worker parents considering having their children vaccinated against HPV (63.1%) was higher than that of nonhealth care worker parents (11.4%). Only 5% of parents had their children previously vaccinated against HPV; however, there was no difference between parents who were health care workers and those who were not. In addition, this rate was relatively low compared to other paid vaccines (49.8, 35.3, and 18.8%, respectively). Parents who had not previously vaccinated their children against HPV were considering getting their children vaccinated, especially if a pediatrician recommended it.Conclusion The parents' high level of health literacy may not be effective in deciding to vaccinate their children against HPV. Therefore, adequate information and awareness should be provided to all parents about HPV vaccination as early as possible for all children of appropriate age. Pediatricians should be given important roles in raising the awareness of parents about childhood HPV vaccination by health authorities.
Keywords: HPV; vaccination; parents; health literacy; health care workers